Subcutaneous fat area at the upper thigh level is a useful prognostic marker in the elderly with femur fracture. Issue 6 (27th October 2021) - Kim, Youn‐Jung; Seo, Dong‐Woo; Ko, Yousun; Hong, Seok‐In; Kim, Kyung Won; Kim, Won Young
Abstract: Background: The aim of this study was to evaluate prognostic value of body tissue composition at the upper thigh level for 1 year mortality in elderly patients with proximal femur fracture. Methods: This retrospective cohort study included consecutive elderly (aged ≥65) patients diagnosed with proximal femur fracture based on the findings of pelvic bone computed tomography (CT) performed at the emergency department of a tertiary care hospital and treated with surgery between 2010 and 2017. The cross‐sectional area of subcutaneous fat and skeletal muscle at the upper thigh level was measured using CT. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for 1 year mortality were estimated using a Cox proportional hazards model. Survival based on the SFA quartiles was assessed using nonparametric Kaplan–Meier survival analysis and compared used log‐rank tests. Results: Among 876 elderly patients included in this study, the median age was 79.0 years, and 646 (73.7%) patients were female. A total of 93 (10.6%) died within 1 year after admission to the emergency department. Survivors had a significantly higher median subcutaneous fat area (SFA) than non‐survivors (170.2 vs. 133.0 cm 2, P  < 0.001), but no significant difference was observed between the skeletal muscle area (median, 156.7 vs. 160.3 cm 2, P  = 0.504) and muscle density (median, 19.0 vs. 19.1 HU, P  = 0.861) of both groups. After adjustment of other clinical characteristics and body compositions, the multivariate Cox proportional hazard analysis showed that SFA (adjusted HR, 0.987; 95% CI, 0.982–0.992; P  < 0.001) was independently associated with 1 year mortality. With 384 deaths during 51 322 person‐months of follow‐up, the median estimated survival duration of all the patients was 92.8 months (95% CI, 80.8–104.7 months). The patients with SFA in the third (165.6–195.0 cm 2 ) and fourth (>195.0 cm 2 ) quartiles showed significantly longer survival duration than those with SFA in the first (<131.4 cm 2 ; median survival time, 51.3 months) and second (131.4–165.5 cm 2 ; median survival time, 88.7 months) quartiles ( P  < 0.001 by log‐rank test). Conclusions: The SFAs measured at the upper thigh level and 1 year mortality are positively associated in elderly patients with proximal femur fracture. SFA may be an independent prognostic biomarker for 1 year mortality of femur fracture.